Customer Relationship Management (CRM) and Recommendation for Implementation in the Defense Industry: A Literature Review - Ngelyaratan, Dodi; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
- The purpose of this article is to explore the benefits of implementing Customer Relationship Management (CRM) in various industries and provide suggestions to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles on the implementation of Customer Relationship Management (CRM) published from 2014 to 2021 regarding the application of the Kaizen method in various industrial sectors and the defense industry. The analysis used is 30 journal article content analysis. The results of the literature review analysis state that the implementation of Customer Relationship Management(CRM) can have benefits for companies, namely CRM can help teams to improve customer satisfaction, help increase customer retention, help better internal communication, help optimize marketing, help maximize business performance, help maximize business performance by increasing up-selling opportunities and cross-selling. CRM in addition to looking for new customers in addition to maintaining the level of satisfaction of existing consumers, knowing the level of company ownership in consumers, namely by knowing consumer needs, knowing consumer needs in the future, namely through the results of transactions that have been carried out and from the results of data analysis. transaction data that has been collected, knowing abnormalities in each transaction activity, namely knowing criminal acts such as fraud and so on, knowing improvements that must be made to the services provided to consumers, being able to analyze transaction data patterns, for example being able to find out the combination of products to be sold at certain times, reducing operational risk, namely by knowing predictions that will occur and mistakes that have been made through customer history. Based on the results of the literature review, Customer Relationship Management (CRM) is recommended to be applied in the defense industry.